Closed-loop temperature management with internet of things technology support in elderly laparoscopic rectal cancer surgery: A randomised controlled trial - Xue Wang; Jiaqi Xu; Liqun Mo; Li Liu; Jun Zhou; Jun Jiang; Yingying Zhang; Yiping Bai (PLoS ONE, 2025)
Background This study investigates the effectiveness of closed-loop temperature management supported by Internet of Things technology in elderly patients undergoing laparoscopic rectal cancer surgery. Methods Eighty-nine patients were randomly assigned to three Groups. The Enhanced with Warming Blanket Group utilized inflatable warming blankets for insulation. The Closed-Loop Thermoregulation Group employed real-time core temperature monitoring and temperature regulation supported by IoT technology. Core temperatures were continuously monitored from entering the operating room to departure from the Post-Anesthesia Care Unit. Postoperative outcomes including time to tracheal extubation, length of stay in the PACU, incidence of postoperative shivering, time to first flatus, time to first oral feeding, and postoperative length of hospital stay were recorded and compared. Results From 30 minutes after anesthesia induction to departure from the PACU, the Closed-Loop Thermoregulation Group exhibited significantly higher core body temperature than the Routine Group ( All P < 0.05). The incidence of hypothermia upon entering and departure from the PACU was significantly lower in the Closed-Loop Thermoregulation Group compared to the Routine Group ( P = 0.005; P = 0.005). The proportion of time spent in hypothermia was significantly lower in both the Enhanced with Warming Blanket Group and the Closed-Loop Thermoregulation Group compared to the Routine Group ( P < 0.001; P < 0.001). Compared to the Routine Group, both the Enhanced with Warming Blanket Group and the Closed-Loop Thermoregulation Group had significantly shorter times to tracheal extubation (P = 0.033; P = 0.006) and length of stay in the PACU ( P < 0.001; P < 0.001), as well as significantly reduced incidence of postoperative shivering ( P = 0.010; P = 0.012). Conclusions IoT-supported closed-loop temperature management maintains core temperatures, reduces hypothermia and shivering, and shortens extubation and recovery times in elderly laparoscopic rectal cancer patients effectively.